APLIKASI ASAM STEARAT SEBAGAI COMPATIBILIZER PADA FILM KOMPOSIT TEPUNG UBI KAYU-LINEAR LOW DENSITY POLYETHYLENE - Sugiarto,Titi Candra Sunarti,Ani Suryani ,Sutrisno, Indah Yuliasih (Department of Agroindustrial Technology, Bogor Agricultural University, 2016)
Mixing of thermo plasticized cassava flour (TCL) with linear low density polyethylene (LLDPE) is faced in polarity differences where TCL as a polar material while LLDPE is a nonpolar material. To get good compound, an additive substances called compatibilizer is needed to modify the polarityof respective component, i.e. stearic acid to give polar group on LLDPE molecules. The objective of this study was to investigate of the use of stearic acid as compatibilizer on TCL-LLDPE composite film. TCL was produced by adding 30 and 40% (w/w) of glycerin to cassava flour (CL). Composite films were formulated based on CL:LLDPE ratio 2:8 and 3:7. The stearic acid dosages used were 5 and 7% (w/w) of LLDPE. The influence of the flour, glycerin, and stearic acid dose on melt flow index, specific gravity, mechanical properties, seal strength, and film clarity were analyzed. The results show that higher composite melt flow index was obtained on composites that use higher stearic acid dosage. Higher composite specific gravity was obtained on composites that use higher CL. Higher CL ratio give composite film lower mechanical properties and seal strength. The best composite film properties was produced from 2:8 CL:LLDPE ratio, 40% glycerin, and 5% stearic acid. The best properties of the composite film are 5.62 MPa in MD tensile strength and 594.27% elongation.Keywords: cassava flour, composite film, stearic acid